Anosmin-1-Like Effect of UMODL1/Olfactorin on the Chemomigration of Mouse GnRH Neurons and Zebrafish Olfactory Axons Development - Di Schiavi, Elia; Vistoli, Giulio; Moretti, Roberta Manuela; Corrado, Ilaria; Zuccarini, Giulia; Gervasoni, Silvia; Casati, Lavinia; Bottai, Daniele; Merlo, Giorgio Roberto; Maggi, Roberto (Frontiers in Cell and Developmental Biology, 2022)
The impairment of development/migration of hypothalamic gonadotropin-releasing hormone (GnRH) neurons is the main cause of Kallmann’s syndrome (KS), an inherited disorder characterized by hypogonadism, anosmia and other developmental defects. Olfactorin is an extracellular matrix protein encoded by UMODL1 (uromodulin-like 1) gene expressed in the mouse olfactory region, along the migratory route GnRH neurons. It shares a combination of a WAP and FNIII repeats, expressed in complementary domains, with anosmin-1, the product of ANOS1 gene, identified as causative of KS. In the present study we have investigated the effects of olfactorin in vitro and in vivo models. The results show that olfactorin exerts an anosmin-1-like strong chemoattractant effect on immortalized GnRH neurons (GN11 cells) through the activation of FGFR and of MAPK pathway. In silico analysis of olfactorin and anosmin-1 reveals a satisfactory similarity at N-terminal region for the overall arrangement of corresponding WAP and FNIII domains and marked similarities between the binding modes of interaction of the WAP domains with the resolved FGFR1-FGF2 complex. Finally, in vivo experiments show that the down modulation of zebrafish z-umodl1 gene (orthologous of UMODL1) in both GnRH3:GFP and omp2k::gap-CFPrw034 transgenic zebrafish strains leads to a clear misorganization and altered fasciculation of the neurites of GnRH3::GFP neurons crossing at the anterior commissure and a significant increase in olfactory CFP+ fibers with altered trajectory. Thus, our study shows olfactorin as an additional factor involved in the development of the olfactory and GnRH systems and proposes UMODL1 as a gene worthy of diagnostic investigation in KS.